2000
DOI: 10.1029/2000jb900041
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle seismic wave velocity: Effects of realistic partial melt geometries

Abstract: Abstract.We investigate seismic wave velocity reduction resulting from the presence of partial melt in the upper mantle. The amount of shear and bulk modulus reduction produced by the presence of a connected network of realistically shaped and naturally organized melt inclusions is found using finite element calculations. The geometries of the inclusions are taken directly from laboratory experiments of mantle melting, with finite element meshes constructed to conform to these shapes. The shear and bulk moduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
356
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(374 citation statements)
references
References 35 publications
16
356
1
1
Order By: Relevance
“…They predict larger variations for higher total melt fractions above 1%. Using melt inclusions as a analogy for a fluid-filled pore space (shear modulus G F of melt or fluid is set to zero), our model is many times more sensitive to porosity changes than the comparable model by Hammond and Humphreys [2000]. Considering that our model is based on an empirical law developed for high porosity sandstone, the V P /V S -lowporosity relationship compares very well with the effect of low-porosity melt inclusions estimated by discrete numerical models.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…They predict larger variations for higher total melt fractions above 1%. Using melt inclusions as a analogy for a fluid-filled pore space (shear modulus G F of melt or fluid is set to zero), our model is many times more sensitive to porosity changes than the comparable model by Hammond and Humphreys [2000]. Considering that our model is based on an empirical law developed for high porosity sandstone, the V P /V S -lowporosity relationship compares very well with the effect of low-porosity melt inclusions estimated by discrete numerical models.…”
Section: Discussionsupporting
confidence: 55%
“…Hammond and Humphreys [2000] show with finite element models that an increase of intergranular partial melt inclusions of around 1% volume fraction could decrease V P and V S at least 3.6% and 7.9%, respectively. They predict larger variations for higher total melt fractions above 1%.…”
Section: Discussionmentioning
confidence: 99%
“…Melt affects velocity through elastic and anelastic effects 20,21,22 , while dissolved water primarily affects velocities through anelastic effects 23,24 . Therefore, using seismic data to discriminate between the presence of melt and water will require determination of the Q structure beneath this region of the mantle.…”
mentioning
confidence: 99%
“…Moreover, the fraction of melt retention in the asthenosphere may cause such a large drop in shear velocity. Inclusion of little more than 1 % melt in the asthenosphere, in addition to the temperature contrast, provides a realistic explanation of this velocity drop (Hammond and Humphreys, 2000;Rychert et al, 2012). Karato (1990) indicated that the presence of H 2 O in olivine weakens the material.…”
Section: Shear-wave Velocity Drop Across Labmentioning
confidence: 99%